Reply to: "Comment on the paper `On the triangular libration points in photogravitational restricted three-body problem with variable mass''' by Varvoglis, H. and Hadjidemetriou, J.D. - Zhang, Ming-Jiang (2012)
Recently Varvoglis and Hadjidemetriou (Astrophys. Space Sci. doi:10.1007/s10509-012-1060-3, 2012; hereafter referred to as paper VH) have raised two points concerning the model of the restricted three-body problem with variable mass presented in our paper (Zhang et al. in Astrophys. Space Sci. 337:107, 2012; hereafter referred to as paper ZZX) and made intensive investigations of this model. These points and investigations are very useful and here we provide some explanation and supplementary specification regarding the model presented in the paper ZZX.
Keywords: Restricted three-body problem; Variable mass